(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The geographical structure of the flora of the National Nature Park «Pyryatynsky» is analyzed in the paper. Typological system of plant species areas according to zonal characteristics, horionimic element and its activity is developed. It was found that species of flora National Park are distributed among 11 type, 1 subtype groups and 39 areas. Horological core of the flora of the National Nature Park «Pyryatynsky» contain Eurasian and Holarctic species with areas in temporal and submeridional zones. A significant part of flora belong to Palearctical, Euro-Mediterranean-Iran-Turanian and European geoelements. Flora of the National Nature Park «Pyryatynsky» is close to the Mediterranean flora. However, part of the Eurasian steppe and desert-steppe elements is minimal, due to the latitudinal location of NNP and total destruction characteristic of these types of florokomplexes. The increased role of cosmopolitical species is the result of penetration of alien flora elements. Location of the National Nature Park «Pyryatynsky» in the valley of Uday and on the verge of fitochorions of regional scale helps to enrich the flora and indicate a significant sozological value of this natural protected area.